A novel electrochemical IL-6 sensor based on Au nanoparticles-modified platinum carbon electrode - Wang, Cai; Xin, Dongyuan; Yue, Qianwen; Wan, Huiyu; Li, Qian; Wang, Ying; Wu, Jingguo (Frontiers in Bioengineering and Biotechnology, 2023)
In this article, based on the specific antigen-antibody binding reaction, we prepared an electrochemical sensor for the detection of interleukin-6 (IL-6). (1(3-dimethylamino-propyl) -3-ethylcarbon diimide hydrochloride/N-hydroxysuccinimide (EDC/NHS) was used to activate carboxyl groups, so that 4-mercaptobenzoic acid (4-MBA) attached to platinum carbon (PC) electrode modified by angular branch Au nanoparticles (AuNPs) could better bind with IL-6 antibody, and finally formed an electrochemical sensor that specifically recognized IL-6. Through the highly specific antigen-antibody reaction, the IL-6 concentration of the samples to be detected. The performance of the sensor was studied by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The experimental results showed that the linear detection range of the sensor for IL-6 was 100 pg/mL-700 pg/mL and the detection limit was 3 pg/mL. In addition, the sensor had the advantages of high specificity, high sensitivity, high stability and reproducibility under the interference environment of bovine serum albumin (BSA), glutathione (GSH), glycine (Gly) and neuron-specific enolase (NSE), which provided a prospect for specific antigen detection sensor.